Redukcjonistyczne i organicystyczne intuicje w wyjaśnianiu karcynogenezy - Juś, Marcin (Wydawnictwo Naukowe UAM, 2013)
Two competing theories of carcinogenesis are functioning in biomedical sciences: the mutation theory (SMT) and the tissue theory (TOFT). The first part of the article presents the basic assumptions of both theories and summarizes the philosophical debate between its proponents. This debate is analyzed in the works of Ch. Malaterre [2007] and J. A. Macrum [2005]. According to these authors, the genetic theory presupposes reductionism and the tissue theory – organicism. The second part of the article analyzes the debate in question in the light of some general views about reduction developed by T. Jones [2004] and K. Paprzycka [2008]. I suggest that from the philosophical point of view we have no reason to think that the reduc-tionist explanation of carcinogenesis is exhaustive or that it is the only appropriate explanation.

W naukach biomedycznych funkcjonują obecnie dwie konkurencyjne teorie karcynogenezy: teoria mutacji (SMT) i teoria tkankowa (TOFT). W pierwszej części artykułu przedstawiam podstawowe założenia obu teorii oraz streszczam dyskusję filozoficzną dotyczącą sporu pomiędzy ich zwolennikami. Spór ten jest przedmiotem analizy w pracach Ch. Malaterra [2007] i J. A. Macrum [2005]. Zgodnie z opinią przytoczonych autorów punktem wyjścia teorii genetycznej jest redukcjonizm natomiast konkurencyjnej teorii tkankowej − organicyzm. W drugiej części artykułu analizuję przedstawioną kontrowersję w świetle ogólnych rozważań nad redukcją prowadzonych przez T. Jonesa [2004] i K. Paprzycką [2008]. Sugeruję iż z perspektywy filozoficznej nie mamy powodu sądzić, że redukcjonistyczne wyjaśnienie karcynogenezy może być wyjaśnieniem wyczerpującym bądź jedynym właściwym.
Reductionist and Organicist Intuitions in the Explanation of Carcinogenesis
Keywords: reductionism; antireductionism; organicism; cancer; carcinogenesis